Formation of positive product ions from substances with low proton affinity in high kinetic energy ion mobility spectrometry. (7th January 2021) - Allers, Maria; Kirk, Ansgar T.; Schaefer, Christoph; Schlottmann, Florian; Zimmermann, Stefan
Abstract : Rationale: Ion mobility spectrometry (IMS) instruments are typically equipped with atmospheric pressure chemical ionization (APCI) sources operated at ambient pressure. However, classical APCI‐IMS suffers from a limited ionization yield for nonpolar substances with low proton affinity (PA). This is mainly due to ion clustering processes, especially those that involve water molecules, inhibiting the ionization of these substances. Methods: High Kinetic Energy (HiKE)‐IMS instruments are operated at decreased pressures and high reduced electric field strengths. As most clustering reactions are inhibited under these conditions, the ionization yield for nonpolar substances with low PA in HiKE‐IMS should differ from that in classical APCI‐IMS. To gain first insights into the ionization capabilities and limitations of HiKE‐IMS, we investigated the ionization of four model substances with low PA in HiKE‐IMS using HiKE‐IMS‐MS as a function of the reduced electric field strength. Results: The four model substances all have proton affinities between those of H2 O and (H2 O)2 but exhibit different ionization energies, dipole moments, and polarizabilities. As expected, the results show that the ionization yield for these substances differs considerably at low reduced electric field strengths due to ion cluster formation. In contrast, at high reduced electric field strengths, all substances can be ionized via charge and/or proton transfer in HiKE‐IMS. Conclusions: Considering the detection of polar substances with high PAs, classical ambient pressure IMS should reach better detection limits than HiKE‐IMS. However, considering the detection of nonpolar substances with low PA that are not detected, or only difficult to detect, at ambient pressure, HiKE‐IMS would be beneficial.